2011
DOI: 10.2214/ajr.10.4441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aggressiveness of Prostate Cancer: Correlation of Apparent Diffusion Coefficient With Histologic Grade After Radical Prostatectomy

Abstract: ADC values were found to be negatively correlated with the postsurgical Gleason grade in patients with prostate cancer. Our results show that ADC values might help to predict prostate cancer, especially for tumors in the peripheral zone. Given the substantial overlap in the ADC values, the addition of other MR parameters, such as volumetry, and technical improvements in diffusion-weighted imaging might improve accuracy in the stratification of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 33 publications
16
101
2
1
Order By: Relevance
“…It has been shown that ADC values were negatively correlated with the postsurgical GS in PCA patients. The ADC was furthermore sufficient to predict the presence of low-grade and high-grade PCA in the peripheral zone (PZ) (14)(15)(16). Regarding T2-weighted (T2W) images, it has been demonstrated that PCA have lower T2 signal intensity (SI) than non-neoplastic tissue (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ADC values were negatively correlated with the postsurgical GS in PCA patients. The ADC was furthermore sufficient to predict the presence of low-grade and high-grade PCA in the peripheral zone (PZ) (14)(15)(16). Regarding T2-weighted (T2W) images, it has been demonstrated that PCA have lower T2 signal intensity (SI) than non-neoplastic tissue (11).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ADC values generated from multiple b-values give an objective measurement of tissue diffusion and are a surrogate for tumor aggressiveness [5,25] . The values broadly change inversely with Gleason score and the trend is lower in higher stage of disease, although there are some overlaps between benign and malignant tissue [5,25,26] . Gains in sensitivity with higher tADC values would be expected to be offset by lower specificity and a balance between these outcome parameters is required.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing PSA levels with subtle changes in ADC raise suspicious of tumor recurrence. ADC values are found to be negatively correlated with the post-surgical Gleason grade in patients with prostate cancer 12 . Our results show that ADC values might help to predict PC, especially for tumors in the peripheral zone.…”
Section: Tumor Localisationmentioning
confidence: 93%
“…Our results show that ADC values might help to predict PC, especially for tumors in the peripheral zone. Given the substantial overlap in the ADC values, the addition of the other MR parameters, such as volumetry and technical improvements in DWI might improve accuracy in the stratification of patient 12 . On DCE-MRI, PC shows early nodular enhancement before the rest of the parenchyma and early washout of contrast medium based on the pathologic microvasculature in the tumor (Fig.…”
Section: Tumor Localisationmentioning
confidence: 99%